PEMFC Semi-Empirical Model Improvement by Reconstructing Concentration Loss - Qinwen Yang; Xuan Liu; Gang Xiao; Zhen Zhang (Energies)
The performance of proton exchange membrane fuel cells (PEMFCs) is greatly affected by their operating parameters, especially at high current densities. An advanced concentration loss model is proposed to improve a semi-empirical model describing PEMFC polarization, with the aim of accurate prediction at the whole current density interval from low to high levels. Experiments are designed to verify the improved semi-empirical model. Model comparison shows that the improved semi-empirical model has a better prediction accuracy and generalization ability than others. The effects of operating parameters and structural parameters on PEMFC performance are analyzed. The results indicate that a relatively high operating temperature, pressure, and gas diffusion layer (GDL) porosity can increase PEMFC performance. The influence of relative humidity and PEM thickness on PEMFC performance is different at low and high current densities. A relatively high humidity can improve PEMFC performance at a low current density, but PEMFC performance will be reduced if the relative humidity is too high at a high current density. A thinner PEM thickness can improve PEMFC performance at a low current density, but PEMFC performance does not necessarily improve with a decreasing PEM thickness at a high current density. Overall, the improved semi-empirical model realizes an accurate analysis of PEMFC performance from a low to high current density.